Phytochemical Screening and Larvicidal Activity of Kebiul (Caesalpinia Bonduc. L) Seed Kernel Against Aedes Aegypti Mosquito - Popi Rantina; Dwi Fitri Yani; Suci Permata Sari; Dany Raihan (Department of Chemistry Faculty of Science and Technology Walisongo, 2022)
Dengue Hemorrhagic Fever (DHF) is caused by an infected A. aegypti mosquito, which can cause serious bleeding, a sudden drop in blood pressure and even death. Kebiul seed kernel extract is thought to contain flavonoid compounds, terpenoids, saponins and steroids that can be used as larvicides. The purpose of this study was to determine the toxicity of the extract, n-hexane fraction, and ethanol fraction of kernel seed (C. bonduc. L) against A. aegypti mosquito larvae. This study used the methods of extraction, phytochemical screening, and toxicity tests by calculating larval mortality. Based on the results of phytochemical screening, extract of kernel seed (C. bonduc. L) contains tannins, flavonoids, alkaloids, steroidal saponins and terpenoids. Toxicity test (LC50 values) of extract, n-hexane fraction, and ethanol fraction of kernel seed (C. bonduc. L) are 368,566 g/mL, 483,010 g/mL, 338,361 g/mL. The LC50 value 1000 ppm has a toxic effect, so the kernel seed has the potential to be used as a larvicide.